Pet sematary [videorecording (DVD)] - Clarke, Jason, 1969-; Seimetz, Amy; Laurence, Jeté, 2007-; Lithgow, John, 1945-; King, Stephen, 1947- (Paramount Home Entertainment, 2019)
Based on the seminal horror novel by Stephen King, Pet Sematary follows Dr. Louis Creed, who, after relocating with his wife Rachel and their two young children from Boston to rural Maine, discovers a mysterious burial ground hidden deep in the woods near the family's new home. When tragedy strikes, Louis turns to his unusual neighbor, Jud Crandall, setting off a perilous chain reaction that unleashes an unfathomable evil with horrific consequences.